Blue Light Enhances Bacterial Clearance and Reduces Organ Injury During Sepsis*. Issue 8 (August 2018) - Lewis, Anthony J.; Zhang, Xianghong; Griepentrog, John E.; Yuan, Du; Collage, Richard D.; Waltz, Paul K.; Angus, Derek C.; Zuckerbraun, Brian S.; Rosengart, Matthew R.
Abstract : Objectives: The physiology of nearly all mammalian organisms are entrained by light and exhibit circadian rhythm. The data derived from animal studies show that light influences immunity, and these neurophysiologic pathways are maximally entrained by the blue spectrum. Here, we hypothesize that bright blue light reduces acute kidney injury by comparison with either bright red or standard, white fluorescent light in mice subjected to sepsis. To further translational relevance, we performed a pilot clinical trial of blue light therapy in human subjects with appendicitis. Design: Laboratory animal research, pilot human feasibility trial. Setting: University basic science laboratory and tertiary care hospital. Subjects: Male C57BL/6J mice, adult (> 17 yr) patients with acute appendicitis. Interventions: Mice underwent cecal ligation and puncture and were randomly assigned to a 24-hour photoperiod of bright blue, bright red, or ambient white fluorescent light. Subjects with appendicitis were randomized to receive postoperatively standard care or standard care plus high-illuminance blue light. Measurements and Main Results: Exposure to bright blue light enhanced bacterial clearance from the peritoneum, reduced bacteremia and systemic inflammation, and attenuated the degree of acute kidney injury. The mechanism involved an elevation in cholinergic tone that augmented tissue expression of the nuclear orphan receptor REV-ERBα and occurred independent of alterations in melatonin or corticosterone concentrations. Clinically, exposure to blue light after appendectomy was feasible and reduced serum interleukin-6 and interleukin-10 concentrations. Conclusions: Modifying the spectrum of light may offer therapeutic utility in sepsis. Abstract : Supplemental Digital Content is available in the text.